HISTORYCY JĘZYKA WOBEC TERMINÓW – TERMINY WOBEC HISTORYKÓW JĘZYKA. GLOSA DO DYSKUSJI - WOŹNIAK-WRZESIŃSKA, EWELINA (Slavia Occidentalis, 2020)
The article has two main goals, one of them being a report on the Third Conference of the Old Polish Linguistic Encounters series, the terms in synchronic and diachronic linguistics and a synthetic discussion of the issues raised during the Congress. In the first, definitely shorter part I discuss the issues presented by the referees. The second part, in turn, is devoted to the analysis of the aforementioned issues from the perspective of the theory of the term. At the end of the article I present science-oriented attitudes that characterize the speakers at the mentioned conference. I ponder if their problems result from their relation to science itself.